Lokalitas Kitab Tajwid Nusantara - Mustafidah, Lailatul; Niam, Khairun (SUHUF, 2024)
So far, the discourse of al-Qur’an studies in Indonesia has only focused on the works of tafsir and translation of the Qur’an, and more needs to be discussed related to tajweed. Likewise, tafsir in Nusantara is characterized by many aspects of locality. Studies on tajweed have also experienced vernacularization in scientific transmission. One of the local works in tajweed is Tanwir al-Qari’ fi Tajwid Kalam al-Bari’ by K. H. M. Mundzir Nadzir. By using Hans Georg Gadamer’s fusion of horizon theory, this article intends to discuss the aspects of locality in it. The research is included in the qualitative research method with the type of library research. The stages are data collection, data classification, reconstructing the data that has been collected, and then processing and interpreting it. The results of this study indicate that the local aspects in Tanwir al-Qari’ fi Tajwid Kalam al-Bari’ are, First, a locality in physical terms. Second, locality in communication. Third, locality in terms of meaning.